Eye darkening as a reliable, easy and inexpensive indicator of stress in fish - Freitas, Renato H. A. [UNESP]; Negrao, Carolina A.; Felicio, Ana Karina C.; Volpato, Gilson L. [UNESP] (Elsevier B.V., 2014)
We expand the use of eye darkening (ED) to indicate non-social stress in the fish Nile tilapia Oreochromis niloticus (L.). ED is easily estimated, not requiring any sophisticated equipment, and is non-invasive, facilitating the collection of several measures of stress over time. In the current study, we showed the following: (i) high- and low-ED occur spontaneously, indicating different fish reactions to adjustments to a novel environment; (ii) fish confinement or air exposure clearly increases ED (air exposure is a stronger stressor than confinement), and the time to restore basal values indicates the severity of the impact of the stressor on the fish (this response is not affected by period of the day, e.g., morning or afternoon); and (iii) in adults, females were more responsive (slower recovery) to 2-min air exposure than to 30-min confinement. (C) 2014 Elsevier GmbH. All rights reserved.
Keywords: Stress; Eye color; Air exposure; Confinement; Nile tilapia